The effect of CSR performance on profitability with CEO’s education and tenure as moderators - Gusti Ayu Agung, Mas Medhayani; Komang Ayu, Krisnadewi (E-Jurnal Akuntansi, 2025)
This research generates empirical proof of how CSR performance influences profitability and determine whether CEO's education level and business education, and CEO's tenure enhance the influence of CSR performance on profitability. Consumer goods manufacturing companies that went public on IDX between 2021 and 2023 constitute the population, with the sample selected through purposive sampling. MRA served as the method for analyzing the data. Results indicate that CSR performance has no significant influence on profitability, CEO’s education level and tenure enhance CSR performance’s influence on profitability, and CEO’s business education weakens CSR performance’s influence on profitability. This study carries theoretical implications that confirm the upper echelon theory and the practical implication is to help manufacturing companies increase profitability by presenting an insight into the relevance of the CEO’s education level and tenure.